Influence of respiratory muscle training on cardiorespiratory response sensitivity and fast kinetics in endurance athletes - Tomiak, T.; Mishchenko, V.; Kuehne, T. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Previous studies have demonstrated that the work of breathing during sustained heavy-intensity exercise has a significant influence on exercise performance (Harms, 2000). Respiratory muscle training (RMT) may cause changes not only in respiratory muscle power-endurance and lung capacities, but also in cardiorespiratory (CRS) chemo-sensitivity, perceptual response and lactate kinetics (Mishchenko V, Monogarov V,1995; Romer LM, McConnel AK, Jones DA, 2002) and in athletes` working capacities. Whether or not these benefits can be achieved by only increasing of respiratory muscle possibilities remains open for debate. It was hypothesized that effects of RMT may be linked with increase of CRS response sensitivity and fast kinetics. The purpose was to determine the effects of RMT to CRS response carbon dioxide sensitivity, fast kinetics and exercise performance. Methods Twenty two male high performance rowers were randomized into two groups and perform for three weeks (18 session) the same program of preseason training: mean weekly predominantly aerobic exercise time of 10,5 hours of rowing (Concept 2). Ten athletes were assigned to RMT group and twelve athletes were received sham respiratory training with the same device (control group). RMT group performed ten repetitions (2 min interval) of 30 inhalation-exhalation (Powerlung) two times a day for three weeks with resistance adjusted (via trial and error) to allow for 30 breathes to be close about ¾ of maximal effort. Before and after three weeks athletes tested for VE response sensitivity (rebreathing, standard rest) and fast kinetics (T50) of VO2, VCO2, VE and HR (transition from 25w) in rowing ergometer exercise at 0,7 VO2 max and performed 2000m all-out rowing simulation. All comparison were made by using ANOVA with repeated measures and significance was set at ** p<0,05. Results The data revealed that RMT produce significant increase in VE response sensitivity: 1,53(0,11) vs. 1,69(0,15) l.min-1 per 1 mm Hg (mean and SD, p<0,05) compared to control: 1,59(0,14) vs. 1,53(0,16) l.min-1 per 1 mm Hg (ns) and in fast kinetics - T50 VE : 39,1(2,7) vs. 31,9 (2,8) s (p<0,05), control - 38,3(2,9) vs. 36,4 (2,7) s (ns); T50VCO2 : 36,9 (2,5) vs. 33,8 (2,9) s (p<0,05), control - 38,0 (2,6) vs. 36,1 (2,8) s (ns) and V50 HR : 21,1 (1,3) vs. 17,6 (1,2) s (p<0,1), control - 20,7 (1,4) vs. 19,1 (1,3) s (ns). There were not significant effects on VO2 peak in 2000m all-out rowing simulation in both groups. But athletes in RMT group compared with control had statistically significant increase of VE peak, mean power for the first 500m distance and decrease of O2 - `cost` for 2000m all-out test ( Fig. 1). Discussion/Conclusion The results revealed that three weeks of RMT improved in CRS response fast kinetics. Such changes were significantly related to changes of lung ventilation sensitivity to carbon dioxide (r=0,67) and VE peak for all-out rowing simulation (r=0,61). There was in RMT group also tendency to increase some measurements of special working capacities. It may be linked via CRS drive mechanism to some possibilities of ventilatory compensation of metabolic acidosis enhancement during sustained heavy-intensity exercise.